2015
DOI: 10.1039/c5ja00137d
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ionization potential of an element and boiling point of the corresponding oxide on the sensitivity of ICP-MS

Abstract: The sampling depth profiles of 19 elements in aqueous solution were obtained. The optimized sampling position depends on the boiling point of the oxides for high-boiling oxides, or the difference between the boiling point and the temperature for high degree of ionization for elements of high ionization potential and low-boiling oxides.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 40 publications
0
33
0
Order By: Relevance
“…Sufficient time is required in the hot ICP to completely vaporize the nanoparticles [31,81,82]. After vaporization, atomization, and ionization, a cloud of mainly elemental ions (for the majority of elements in the Periodic Table) is produced [83,84].…”
Section: Conversion Of Droplets and Nanoparticles Into Elemental Ionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sufficient time is required in the hot ICP to completely vaporize the nanoparticles [31,81,82]. After vaporization, atomization, and ionization, a cloud of mainly elemental ions (for the majority of elements in the Periodic Table) is produced [83,84].…”
Section: Conversion Of Droplets and Nanoparticles Into Elemental Ionsmentioning
confidence: 99%
“…prior to the counting electronics. This results in a nonlinear response for intense signals from individual nanoparticles [81]. For a detector and processing electronics with a dead time of 50 ns, a peak signal of 2,000,000 c/s, corresponding to just 100 counts in 50 μs, would on average result in a measured signal of 90 counts (i.e., a 10 % error).…”
Section: Limited Dynamic Range Of Pulse Counting Detection Of Individmentioning
confidence: 99%
“…The isotopes 12 C and 13 C were monitored by ICP-MS in addition to the internal standards 89 Y and 103 Rh and further elements of interest such as 27 Al, 31 P and 57 Fe (see fractogram of soil extracts in Figure S1 of the Supplementary Information). The instrument was operated in helium collision cell mode to minimise spectral interferences by cluster ions and to suppress the 12 C signal to a suitable intensity range.…”
Section: Asymmetric Flow Field Flow Fractionation Online With Icp-msmentioning
confidence: 99%
“…It is generally accepted that the aerosols of standard solution are completely vaporized in the ICP at typical ICP-MS sampling depth of 10 mm. 32 However, single particles of diameter as small as 250 nm may not be completely vaporized at the same sampling depth because the residence time of the particles at the sampling position is insufficient for complete vaporization. Calibration by standard solution, therefore, becomes inaccurate.…”
Section: Introductionmentioning
confidence: 99%
“…We have previously reported that the shape of the ICP-MS sampling depth profile for standard solutions is strongly dependent on the boiling point of the dry aerosols of the solutions. 32 Analytes that give high boiling oxides as dry aerosols generally have peak positions at higher sampling depths because the aerosols start to vaporize only after the gas temperature reaches the boiling point and the vaporization process takes time to finish. We will show that the boiling-point requirement for aerosol vaporization applies to single particles in the ICP.…”
Section: Introductionmentioning
confidence: 99%